Tax Planning To Increase The Value Of The Company - Noviari, Naniek; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2020)
The objectives of this study are (1) to examine the effect of tax planning on firm value, (2) to examine the effect of good corporate governance on firm value, and (3) the moderating effect of good corporate governance on the relationship of tax planning and firm value. The study population is all companies registered in the Indonesian Corporate Governance Forum (FCGI) in 2012-2017. The sample was chosen based on purposive sampling technique. The number of companies selected as a sample of 9 companies, thus obtained 54 observations during the study period. The study uses descriptive statistical analysis and moderated regression analysis (MRA). The results of the study prove (1) tax planning does not increase company value, (2) good corporate governance has a positive effect on company value, and (3) good corporate governance moderates the effect of tax planning on firm value. Key Words: Tax Planning; Company Value; Good Corporate Governance.